Manure production and mineral excretion in feces of gilts fed ractopamine - Watanabe, Pedro Henrique [UNESP]; Thomaz, Maria Cristina [UNESP]; Pascoal, Leonardo Augusto Fonseca [UNESP]; Ruiz, Urbano Dos Santos [UNESP]; Daniel, Everton [UNESP]; Amorim, Alessandro Borges [UNESP] (Editora da Universidade Estadual de Maringá (EDUEM), 2013)
A study was conducted to evaluate the feces+urine produced per animal (FUPA), dry matter, mineral matter, organic matter, nitrogen, phosphorus, potassium and sulfur in feces of gilts fed diets with increasing levels of ractopamine (0, 5, 10 and 15 mg kg-1 of diet). A total of 468 finishing gilts were allotted into 36 pens. In two days of each week, feces and urine were daily sampled in four pens per treatment, quantifying the feces+urine. To determine the characterization of feces, two samples per week were taken daily, in nine pens per treatment. It was used a split plot design, considering the ractopamine level as the plot and the weeks as the subplots. There was no reduction in nitrogen amount in feces. An interaction was detected between ractopamine concentrations and weeks for FUPA and phosphorus, potassium and sulfur in feces. Ractopamine addition in diets for gilts has reduced the feces+urine production and nitrogen and phosphorus excretion. Higher values estimated for potassium content in feces of animals fed diets with 10 and 15 mg of ractopamine kg-1 were found between the second and third week. Increasing levels of ractopamine from 5 to 15 mg kg-1 promoted higher excretion of sulfur over the weeks of supply.

Objetivou-se avaliar a produção de fezes+urina por animal e teores de matéria seca, matéria mineral, matéria orgânica, nitrogênio, fósforo, potássio e enxofre nas fezes de suínos alimentados com dietas contendo concentrações crescentes (0, 5, 10 e 15 mg kg-1 de dieta) de ractopamina. Foram utilizadas 468 fêmeas suínas, alojadas em 36 baias de piso compacto. A cada semana foram realizadas duas colheitas diárias de fezes e urina, de quatro baias por tratamento e duas colheitas semanais, de nove baias por tratamento, para determinação da composição fecal. Utilizou-se o delineamento em blocos, em esquema de parcelas subdivididas, sendo as parcelas as concentrações de ractopamina e as semanas como subparcelas. Não houve redução na quantidade de nitrogênio excretado. Observou-se interação entre concentração de ractopamina e semana, para a produção de fezes+urina por animal e para os teores de fósforo, potássio e enxofre nas fezes. A ractopamina na dieta reduz a produção de fezes+urina e a excreção de nitrogênio e fósforo nas duas semanas iniciais. Foram encontrados maiores valores estimados para o teor de potássio nas fezes de animais alimentados com dietas contendo 10 e 15 mg de ractopamina kg-1 entre a segunda e terceira semanas. O aumento na concentração de ractopamina de 5 até 15 mg kg-1 promove maior excreção de enxofre em função das semanas.
Produção de dejetos e excreção mineral nas fezes de fêmeas suínas alimentadas com ractopamina
Keywords: additive; Environmental impact; Finishing; Mineral; Sus scrofa; Aditivos; Impacto ambiental; Terminação; Minerais; Sus scrofa